Active Rheology Control of Cementitious Materials - De Schutter, Geert (Modern Concrete Technology, 2023)
This book reports on cutting-edge research within the new field of active rheology control of cementitious materials, presenting new ideas developed within the ERC Advanced Grant Project, SmartCast (hosted at Ghent University), which extend the possibilities of admixtures and additions beyond current options. The research presented here develops a new method of actively controlling the rheology of fresh concrete during casting operations by incorporating specially designed responsive components. This results in real-time changes to the rheological behaviour of the cementitious material, allowing the user to intervene actively after the cementitious material has left the mixing phase. This newly gained agility contributes to increased processing speed and placement reliability in the case of traditional casting methods and can also facilitate advanced 3D concrete printing. The different routes followed to achieve this Active Rheology Control are explained within. The book suits researchers and innovative practitioners and is the first comprehensive text to present these new findings. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.